2011
DOI: 10.1097/mcp.0b013e3283431674
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema and chronic obstructive pulmonary disease in coal miners

Abstract: Latest studies further support the association of emphysema and COPD with coal dust exposure. Increased cumulative exposure may also increase risk of death from these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…Previous studies have well documented the association between long‐term exposure to coal mine dust and mortality, even after adjustment for smoking [3,4]. Further, the association of emphysema and COPD with coal dust exposure has been reported, and increased cumulative dust exposure (CDE) may also increase the death rate of these diseases [1,5]. With enforcement of occupational exposure limits for coal mine dust, declined CWP prevalence from 11.2% to 2.0% is found among underground coal miners [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have well documented the association between long‐term exposure to coal mine dust and mortality, even after adjustment for smoking [3,4]. Further, the association of emphysema and COPD with coal dust exposure has been reported, and increased cumulative dust exposure (CDE) may also increase the death rate of these diseases [1,5]. With enforcement of occupational exposure limits for coal mine dust, declined CWP prevalence from 11.2% to 2.0% is found among underground coal miners [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Coal workers’ pneumoconiosis (CWP) is a slowly progressive lung disease caused by inhalation and deposition of coal mine dust in the lungs, and it is one of the most common occupational diseases worldwide [ 1 , 2 , 3 , 4 ]. Although many measures have been used to prevent CWP, it is still an international public health issue [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that individuals who were diagnosed with pneumoconiosis frequently died of COPD. Although the association between COPD and pneumoconiosis is unclear [Meijers et al, ], there is a known association between exposure to coal dust and COPD [Santo Tomas, ]. Prevention of respiratory failure may be especially important for individuals who died at home (36%).…”
Section: Discussionmentioning
confidence: 99%